(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the outcomes of simple urethral dilatation procedure for the management of short segment urethral strictures. Study Design: Prospective study Place & Duration of Study: This study was conducted at the Department of Surgery, Surgical Unit A, Ayub Teaching Hospital Abbottabad from January 2016 to December 2018. Materials and Methods: Fifty two patients who presented with simple short segment urethral strictures were included. Patients’demographics including age, clinical presentation and etiology of strictures were recorded after written consent. Retrograde urethrography was performed. All patients received simple urethral dilatation under local anesthesia with an antibiotic and steroid instillation after the procedure. Pre- and post-operative maximum urinary flow rate on uroflowmetry and postvoid residual urine (PVR) on ultrasound were noted.Follow-up was taken at 4, 12 weeks and at 1 year. Overall improvement and recurrence rate were recorded at final follow-up. Results: The mean age of patients was 37.6±12.2 years. Majority of patients 42 (80.77%) had weak urine stream. Forty six (88.46%) patients had iatrogenic urethral strictures and 6 (11.54%) had idiopathic strictures. There was a significant improvement regarding maximum urinary flow rate and PVR at 1, 3 months and at 1 year post-operatively (p=0.0001). At final follow-up, 47 (90.38%) patients showed full improvement. Recurrence was seen in 5 (9.62%) patients. Conclusion: Simple urethral dilatation with an addition of antibiotics and steroid is safe and effective treatment modality with fewer complications rate.